Dual inorganic–organic flocculating systems for treatment of oil sands tailings - Mahmoudkhani, A.; Tellakula, R.; Stewart, K.; Watson, P.; Kolla, H. (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
One of the major operational and environmental challenges facing Canada oil sands mining is the separation of water from the fines in tailing ponds in order to accelerate consolidation of tailings and to strengthen mine deposits so they can be reclaimed. Energy Resources Conservation Board (ERCB) Directive 074, released in February 2009 by the Alberta government, urges oil sands producers to accelerate the pace of developing tailings technologies for the consolidation and reclamation of tailings ponds. With no unique and acceptable solution yet in sight, research is now focusing on schemes which utilise more than one technology and combining them into a solution package which is both technically and economically viable.